2015
DOI: 10.1016/j.ijpam.2015.09.001
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of community-associated methicillin-resistant Staphylococcus aureus among outpatient children in a tertiary hospital

Abstract: Background and objectivesThe emergence of methicillin-resistant Staphylococcus aureus (MRSA) infections among previously healthy persons in community settings, without exposure to health care facilities, has been noted recently. Colonization rates of community-associated MRSA (CA-MRSA) have been reported to range from 0 to 9.2 percent. The nose and open skin areas are considered the most important sites for colonization. The aim of our study was to assess the prevalence and to describe the antibiotic susceptib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 19 publications
2
19
1
Order By: Relevance
“…Vancomycin showed appreciable sensitivity of 62.8 % against MRSA and hence proves to be an effective treatment option in comparison to other drugs. Previous studies from Saudi Arabia also show low vancomycin resistance among MRSA strains (Baddour et al, 2006;Alaklobi et al, 2015). As in our case, resistance to cotrimazole has been reported to be high (Yezli et al, 2013).…”
Section: Resultssupporting
confidence: 76%
“…Vancomycin showed appreciable sensitivity of 62.8 % against MRSA and hence proves to be an effective treatment option in comparison to other drugs. Previous studies from Saudi Arabia also show low vancomycin resistance among MRSA strains (Baddour et al, 2006;Alaklobi et al, 2015). As in our case, resistance to cotrimazole has been reported to be high (Yezli et al, 2013).…”
Section: Resultssupporting
confidence: 76%
“…32 In the present study, the prevalence varied across different age groups, with the lower prevalence in the first 12 months of life and the prevalence was more common in children aged more than 10 years of age and similarly male children found to have a higher prevalence rate than the female children which was found to be statistically significant which might be due to the higher exposure to the community and similar type of findings was also quoted in the studies conducted by Miller M et al and Regev-Yochay G et al 33,34 In the current study we found the antibiotic resistance pattern was very high for erythromycin, ciprofloxacin and cephalosporins and the highest sensitivity pattern was observed for vancomycin followed by linezolid and pipercillin (>90%) and the present results was found to be in par with the study done by F. Alaklobi et al in Saudi Arabia. 26 An Indian study had also shown that the levels of CA-MRSA resistant to vancomycin, linezolid, clindamycin, and gentamicin were low, and ciprofloxacin and cotrimoxazole resistance was common and in the present study also the cotrimoxazole resistance was found to be more common (25%), which is a commonly used antibiotic for pediatric patients. 35 Compared to the present study, a comparatively lower rate of resistance was found in the study conducted by Oguzkaya-Artan M, et al, where erythromycin resistance was noted in 6 of the 36 isolates (16.7 %) and clindamycin resistance was present in 3 of the 36 isolates (8.3% total, 6.2 consecutive and 2.1% inducible); all tested isolated were susceptible to vancomycin, as noted in our study.…”
Section: Discussionsupporting
confidence: 66%
“…[23][24][25] The results of the present study is almost in par with the previous Indian studies where we found the overall prevalence of S. aureus was 26.7% and the prevalence of MRSA in the present study was 6.4% and similarly a study done at Saudi Arabia had also reported the prevalence rate of MRSA as 4.6% and the same study had also shown the prevalence of MRSA as 23.2% among the S. aureus carrier patients which is almost similar to the present study where we found the prevalence of MRSA among S.aureus carrier patients was 24.1%. 26 In another study from Andhra Pradesh, India, a carriage rate of 16% for S. aureus (19% MRSA) was documented. 27 Studies from Taiwan and the U.S. have documented prevalence of nasal carriage of S. aureus among children ranging from 16-23% respectively.…”
Section: Discussionmentioning
confidence: 95%
“…Similarly insignificant variation in MRSA isolation rate from, nasal, fomite and hand (p>0.05) found in this study is similar to findings of Loren and Binh [ 30 ], which have suggested that nasal colonization is not the only route for pathogenesis of CA-MRSA infection and that skin-skin and skin-fomite contact could represent important transmission routes. Nasal carriage of MRSA is an important risk factor for subsequent MRSA infection and transmission as the bacterium is transmitted to the nares by contaminated hands and from surfaces where it can survive for months [ 31 ].…”
Section: Discussionmentioning
confidence: 99%